IMPLEMENTATION OF THE YBM PLN ZAKAT PROGRAM AS AN EFFORT TO REDUCE POVERTY: IMPLEMENTATION OF THE YBM PLN ZAKAT PROGRAM AS AN EFFORT TO REDUCE POVERTY - Salim, Amir; Roby Candra Yudha, Ana Toni; Masruchin; Hamka Lubis, Rusdi; Purnamasari, Anggun (OECONOMICUS Journal of Economics, 2026)
In fact, the problem of poverty has not been resolved to date. The State Electricity Company Baitul Maal Foundation (YBM PLN) in its zakat program provides assistance efforts to reduce the level of poverty in the city of Palembang. From the results of observations it is known that the management of zakat funds carried out in the YBM PLN program is productive and consumptive zakat funds, which the program is a gift from. business capital and school scholarships to the needy and poor. This research is a type of qualitative research. Data collection techniques use Observation, Interview, Documentation methods. From the research results, the strategy implemented by YBM PLN can help the welfare of the community with the existence of a productive and consumptive zakat program managed by YBM in PT. PLN (Persero) UIP3B UPT Palembang.